Can Malaysia transit into K-economy dynamic challenges, tough choices and the next phase - Abdulai, David (Pelanduk, 2004)
The book is divided into 2 phases. The first phase provides information about Malaysia's movement to the K-economy, it is more of a general information for those who are less familiar with the effort. The second phase deals with some of the tough challenges ahead and the tough choices the leadership in the country will have to make in the next phase as the country moves to the K-economy and a look into the post K-economy era.